2002
DOI: 10.1002/dc.10219
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemistry of serous effusion specimens: A comparison of ThinPrep® vs. cell block

Abstract: The ThinPrep Processor is gaining popularity in both gynecologic and nongynecologic cytologic samples, including effusion specimens. We compared immunocytochemical results on ThinPrep and cell-block preparations from the same effusion specimen with antibodies commonly used in effusion cytopathology. Samples from 17 reactive effusions and 79 effusions with metastatic adenocarcinomas were each prepared as monolayer ThinPreps and formalin-fixed, paraffin-embedded cell blocks. All slides were immunostained with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
1
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 21 publications
3
67
1
5
Order By: Relevance
“…A previous study exploring the use of immunocytochemistry in effusion specimens concluded that for non-nuclear immunostains (such as polyclonal CEA, B72.3, and Ber-Ep4), the use of ThinPrep cytospin preparations (Hologic, Inc, Marlborough, Mass) provided results comparable to those from cell block sections. 22 Unlike the previous study, the results presented by Ueda et al indicated greater immunoreactivity for MOC-31 in effusion cytology specimens prepared as cytologic smears (100%) rather than as ethanol-fixed cell blocks (44%) or formalin-fixed cell blocks (38%). 14 In conclusion, we found MOC-31 to be an excellent marker for distinguishing reactive mesothelial cells/mesothelioma from metastatic adenocarcinoma in effusion specimens from various primary tumor sites of origin, with high sensitivity (89%) and specificity (100%).…”
Section: -18contrasting
confidence: 58%
“…A previous study exploring the use of immunocytochemistry in effusion specimens concluded that for non-nuclear immunostains (such as polyclonal CEA, B72.3, and Ber-Ep4), the use of ThinPrep cytospin preparations (Hologic, Inc, Marlborough, Mass) provided results comparable to those from cell block sections. 22 Unlike the previous study, the results presented by Ueda et al indicated greater immunoreactivity for MOC-31 in effusion cytology specimens prepared as cytologic smears (100%) rather than as ethanol-fixed cell blocks (44%) or formalin-fixed cell blocks (38%). 14 In conclusion, we found MOC-31 to be an excellent marker for distinguishing reactive mesothelial cells/mesothelioma from metastatic adenocarcinoma in effusion specimens from various primary tumor sites of origin, with high sensitivity (89%) and specificity (100%).…”
Section: -18contrasting
confidence: 58%
“…Gong et al evaluated the immunoreactivity on TP versus CB and reported that both techniques performed equally, except for nuclear stains (Ki67, PCNA and p53), where both the frequency and intensity were significantly reduced on TP compared to CB [35]. Jing et al evaluated the cellular morphology as well as frequency and intensity of IMS in CB prepared directly by thrombin clot, HistoGel, or fixed in CytoLyt (methanol based) then prepared by HistoGel.…”
Section: Preparations For Ancillary Testing Immunostaining (Ims)mentioning
confidence: 99%
“…Nonformalin fixatives have been developed specifically to overcome the dilution of diagnostic fragments by blood and precipitated serum proteins. There are many reports of successful IHC staining on cytology specimens using a variety of preanalytic ''platforms,'' including direct smears 5 ; various monolayer preparations, such as ThinPrep (Hologic Inc, Marlborough, Massachusetts) 6,7 ; SurePath (BD Diagnostics, Franklin Lakes, New Jersey) 8 ; cytospin preparations 1,9 ; and cells removed from a stained, cover-slipped smear and transferred to another slide 10,11 ; or paraffin-embedded cell blocks prepared with or without formalin. 9,[12][13][14][15] There are no data on the number of laboratories using these different preanalytic IHC platforms in the United States.…”
mentioning
confidence: 99%